Can the establishment of national sanitary cities better resist the impact of COVID-19? - Tianqi, Gan; Chunyan, Zhang; Renjun, Shen; Bo, Li (Frontiers in Public Health, 2023)
The global spread of the COVID-19 has brought profound reflection on building a global public health security system. This paper uses the urban data during the COVID-19 epidemic in China in 2020 to evaluate the effect of the National Sanitary City (NSC) policy on the prevention and control of COVID-19 epidemic in different stages. We found that the NSC policy can curb the occurrence and transmission of the epidemic effectively after controlling a series of factors such as urban characteristics, population mobility and pathogen transmission. Compared with Non-NSCs, the NSCs can better control the number of infected people, infection rate and transmission rate, even this performance is more intense when the epidemic enters the sporadic distribution stage gradually. The heterogeneity analysis shows that the impact of NSC policy on the prevention and control of COVID-19 is different in terms of economic development level and population size. To a certain extent, the NSC policy has blocked the spread of viruses by continuously improving the urban medical and health system, strengthening the publicity of infectious disease prevention and control knowledge.